Bioactivities of Gynura spp. and phytochemical investigations of Gynura Bicolor / Teoh Wuen Yew - Teoh, Wuen Yew (2016)

(untitled)
Gynura bicolor and Gynura procumbens which belong to the botanical family of Compositae are widely used by locals as natural remedies in treating hypertension, diabetes and colon cancer. In this study, methanol, hexane, ethyl acetate and water extracts of both Gynura spp. were investigated for antioxidant and cytotoxic activities. Among the extracts of G. procumbens, methanol extract demonstrated better DPPH radical scavenging activity and inhibition of ?-carotene bleaching, while hexane extract showed stronger metal chelating activity. The ethyl acetate extract of G. procumbens with the highest total phenolic content (TPC) exhibited moderate cytotoxicity against HT-29 and HCT 116 colon cancer cells. Among the extracts of G. bicolor, ethyl acetate extract with the highest TPC demonstrated the strongest ability in scavenging DPPH radicals, metal chelating, inhibition of ?-carotene bleaching and cytotoxicity towards HCT 116 and HCT-15 colon cancer cells. The ethyl acetate extract induced apoptotic and necrotic cell death on HCT 116 cells determined by microscopy observation (acridine orange/ethidium bromide staining) and flow cytometry (annexin-V/PI) methods. Both Gynura spp. exerted no damage to CCD-18Co normal colon cells. The acute oral toxicity study indicated that methanol extracts of both Gynura spp. have negligible level of toxicity when administered orally and have been regarded as safe in experimental rats. Six chemical constituents, 5-p-trans-coumaroylquinic acid (1), 4-hydroxybenzoic acid (2), rutin (3), kaempferol-3-O-rutinoside (4), 3,5-dicaffeoylquinic acid (5) and kaempferol-3-O-glucoside (6) were isolated and identified from ethyl acetate extract of G. bicolor. Whilst, guanosine (7) and 5-O-caffeoylquinic acid (8) were successfully isolated and identified from water extract of G. bicolor. These eight chemical constituents were isolated from G. bicolor leaves for the first time, except rutin (3). The 3,5-dicaffeoylquinic acid (5), guanosine (7) and 5-O-caffeoylquinic acid iv (8) showed selective cytotoxicity against HCT 116 cancer cells compared to CCD-18Co normal cells. Cell death and cell cycle arrest effects were observed when HCT 116 cells were treated with 3,5-dicaffeoylquinic acid (5) and 5-O-caffeoylquinic acid (8). The addition of cell impermeable catalase and reduced glutathione protected HCT 116 cells from cell death and cell cycle arrest effects. It was also observed that 3,5-dicaffeoylquinic acid (5) and 5-O-caffeoylquinic acid (8) generated extracellular hydrogen peroxide and green pigment (presumably quinone products) which contributed to cell death and cell cycle arrest. Current investigation revealed that the anti-proliferation effect of guanosine (7) on HCT 116 cells was resulted from cell cycle arrest associated with the activation of ERK1/2, p38 and JNK. The decreased activation of AMPK was also observed. Furthermore, the cell cycle arrest was accompanied by decreased of cyclin D1 level. These observations suggest that cell cycle arrest induced by guanosine (7) may be mediated through activation of ERK1/2, p38 and JNK pathways along with attenuation of AMPK pathway. The findings in present study provided scientific validation on the use of both Gynura spp. as natural remedies in folk medicine. Further studies on the mutagenic and toxicity effect over a longer period of time involving detection of effects on vital organ functions should be carried out to ensure that the plants are safe for human consumption.